2021
DOI: 10.1088/1361-6463/abf0ef
|View full text |Cite
|
Sign up to set email alerts
|

An electrostatic scheme realizing the complete interception of fog droplets by corona discharge-induced ion wind

Abstract: The interception of fog is of great significance for industrial production and human activities. Owing to the simple structure and convenient installation, the fog mesh is widely adopted to intercept droplets in industrial and practical applications. However, the interception mechanism and requirements in high droplet concentration, result in a low inherent interception efficiency. Therefore, a novel method that can completely intercept fog droplets and enhance the local droplets number concentration by changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…137 Apart from charging the collector, charging the droplets could also promote fog collection. Using a corona emitter to spatially electrify the fog droplets (i.e., conduction electrification), the charged droplets are repulsed by the emitter to overcome the aerodynamic drag force (Figure 5a) [138][139][140] and directly propelled toward the collector. Such a method could result in the collection of approximately 30 mL of water within 30 min, which is in striking contrast to its counterpart without the use of electricity (Figure 5b).…”
Section: Electricity-promoted Phase Transition-related Applicationsmentioning
confidence: 99%
“…137 Apart from charging the collector, charging the droplets could also promote fog collection. Using a corona emitter to spatially electrify the fog droplets (i.e., conduction electrification), the charged droplets are repulsed by the emitter to overcome the aerodynamic drag force (Figure 5a) [138][139][140] and directly propelled toward the collector. Such a method could result in the collection of approximately 30 mL of water within 30 min, which is in striking contrast to its counterpart without the use of electricity (Figure 5b).…”
Section: Electricity-promoted Phase Transition-related Applicationsmentioning
confidence: 99%
“…21 Ionic wind generated by the corona discharge process was used to intercept the fog stream and capture fog droplets. 22,23 Corona discharge and cooling have been coupled to harvest the fog and water vapor in the wet flue gas. 24 The deposition efficiency depends on the Stokes number.…”
Section: Introductionmentioning
confidence: 99%
“…An active fog collection approach by using the corona discharge and electric field has recently attracted much attention. Droplets in the fog are charged by the corona discharge, and the deposition efficiency can be greatly enhanced (>1.0) by the electric field . A field experiment demonstrated that an electrostatic fog collector provides a 60% better fog collection rate than a standard mesh-like fog collector .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corona discharge, as a common gas discharge, has been widely used in industrial production and biological technologies, such as material processing [1–4], energy conversion [5–7], environmental governance [8–12], aerospace [13, 14] and agricultural food [15, 16]. Owing to the sharp tip, the needle electrode is always a preferred and favoured structure as the discharge electrode to study the discharge characteristics [17].…”
Section: Introductionmentioning
confidence: 99%